PERINGKAT SOLVABILITAS LAYANAN PEMERINTAH DAERAH KABUPATEN/KOTA DI PROVINSI BALI - purnamasari sp, ana tresna; Dwirandra, A.A.N.B. (E-Jurnal Akuntansi; Vol 10 No 3 (2015), 2015)
Service-level solvency of local government as the capacity of local government to supply and maintain the level of services it provides to the community by using  the index  ratio of  total asset per capita, index ratio of total equities per capita, indeks ratio of total fixed  assets per capita, index ratio of total expenditure per capita, and index ratio of total capital expenditure per capita. The aim of this research is to find determine the service-level solvency of Local Government in the  Province of Bali during the period of 2010-2013. Method of determining the sample is sampling jenuh, where all the population to be sample in to 9 of local government in the  Province of Bali. Results of analysis show that all local Kabupaten Badung was the best local government compared with other regency local governments,but Kabupaten Buleleng  was the worst local government in the Province of Bali.
Keywords: service-level solvency, local government